2021
DOI: 10.1080/17461391.2021.1883124
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation and repeated sprint ability: No effect on sprint performance or ratings of perceived exertion

Abstract: The role of transcranial direct current stimulation (tDCS) as an ergogenic aid is receiving attention from scientists to optimize sport performance. Most studies have examined the effects of tDCS on endurance performance during continuous tasks, while the effect of tDCS on high-intensity intermittent tasks has been less investigated. Therefore, this study aimed to explore the acute effects of tDCS on sprint performance and ratings of perceived exertion (RPE) during a repeated sprint ability (RSA) task. Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
1
11
1
Order By: Relevance
“…As in the present study, other studies have found no positive effects of a-tDCS on strength development in healthy participants [ 23 ], nor relevant effects on jumping performance [ 39 ], and also failed to show the effectiveness in improving sprint performance or reducing RPE during repeated sprint tasks [ 40 ]. Assuming that the ability to generate force is dependent on neural activity (i.e., synchronisation of motor units, as well as intermuscular coordination) and assuming that a-tDCS could facilitate this situation [ 41 ], further research is warranted to provide a better understanding of the effects of a-tDCS on diverse training programs and populations.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…As in the present study, other studies have found no positive effects of a-tDCS on strength development in healthy participants [ 23 ], nor relevant effects on jumping performance [ 39 ], and also failed to show the effectiveness in improving sprint performance or reducing RPE during repeated sprint tasks [ 40 ]. Assuming that the ability to generate force is dependent on neural activity (i.e., synchronisation of motor units, as well as intermuscular coordination) and assuming that a-tDCS could facilitate this situation [ 41 ], further research is warranted to provide a better understanding of the effects of a-tDCS on diverse training programs and populations.…”
Section: Discussioncontrasting
confidence: 46%
“…This effect could be of interest when looking for post-activation potentiation performance enhancement, the improvement of which has been studied using a variety of techniques [ 47 , 48 ]. However, it has recently been shown that the use of a-tDCS for 15 min did not improve CMJ in young trained participants [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, non-invasive brain stimulation over the DLPFC has improved strength endurance performance while reducing RPE (Alix-Fages et al ., 2020). On the other hand, in line with the absence of MF effects on power tasks, non-invasive brain stimulation over the DLPFC does not significantly affect power tasks performance such as CMJ (Romero-Arenas et al ., 2019), MVC (Alix-Fages et al ., 2019) or sprint (Alix-Fages et al ., 2021, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study with elite archers in 'real-world' competition, Mehrsafar et al (2020) demonstrated that applying tDCS with the anode electrode (þ) over the left DLPFC and the cathode (-) over the right DLPFC (þF3/ÀF4 montage) increased vigor and decreased the perceived fatigue, and tension (assessed by the Brunnel Mood Scale) as well as somatic and cognitive anxiety (assessed by the Competitive State Anxiety Inventory 2). However, it should be noted that other studies did not reproduce tDCS induced positive findings on perceived fatigue (i.e., RPE) in non-athletes during vigorous continuous (Okano et al, 2017) or repeated sprint exercise (Alix-Fages et al, 2021).…”
Section: Introductionmentioning
confidence: 76%